Starch-based film incorporated with clitoria ternatea flower extracts as pH indicator - Hazrulrizawati, Abd Hamid; Roziasyahira, Mutaza; Izzah Hayati, Yahya; Zeyohannes, Senait Sileshi (Trans Tech Publications, 2021)
The present study demonstrated the evaluation of starch-based film formulated with Clitoria ternatea flower extracts as a pH indicator. Maceration, sonication, and infusion extraction were employed to determine the percentage yield of the flower extracts. Extract solutions (1 mg/mL) were subjected to UPLCQTOF/MS to detect and identify the chemical constituents of C. ternatea. UV-Vis analysis was done by treating the extracts (4 mg/mL) with prepared buffer solution in various pH values (2.0–11.0), and the absorbance was observed within a broad range of wavelength (400–700 nm). Approximately 100 mL solution of 4 g starch, C. ternatea extracts, and glycerol (19 g plasticiser/100 g starch) in distilled water underwent gelatinisation to form the desired thin film. The functional group presented in the film and raw materials were detected and defined by analysis through FTIR spectroscopy. From the results, the maceration technique produced a higher yield of extracts with 41.48% compared to the sonication and infusion methods. Varied colours of C. ternatea solution were observed at different pH values. At pH lower than 3, the extract solution was light red to purple, while at a higher pH, i.e., towards increasing basic pH (4, 5, 6, 7, 8, and 9), the colour can be perceived as blue. The gelatinisation process produced a blue smooth thin layer of film. FTIR analysis showed that all samples contain a C-O bond (3300 cm-1). Starch-based film formulated with C. ternatea as a pH indicator can be applied to detect the food spoilage in food wrapper and packaging production.